Insulin Growth Factor Binding Protein 7 (IGFBP7)-Related Cancer and IGFBP3 and IGFBP7 Crosstalk - Jin, Li; Shen, Fan; Weinfeld, Michael; Sergi, Consolato (Frontiers in Oncology, 2020)
The insulin/insulin-like growth factors (IGFs) have crucial functions in the growth, differentiation, and proliferation of healthy and pernicious cells. They are involved in coordinated complexes, including ligands, receptors, binding proteins, and their proteases. However, the systems can become dysregulated in tumorigenesis. Insulin-like growth factor-binding protein 7 (IGFBP7) is a secreted protein belonging to the IGFBP superfamily (also termed GFBP-related proteins). Numerous studies have provided evidence that IGFBP3 and IGFBP7 are involved in various cancers, including hepatocellular carcinoma (HCC), breast cancer, gastroesophageal cancer, colon cancer, prostate cancer, among many others, but very few suggest an interaction between these two molecules. In studying several cancer types in our laboratories, we found that both proteins share some crucial signaling pathways. The purpose of this review is to present a comprehensive overview of the relationship between IGFBP7 and cancer, as well as highlighting IGFBP3 crosstalk with IGFBP7 reported in recent studies.